Expression Levels of Genes Encoding Proteins Involved in the Cell Wall–Plasma Membrane–Cytoskeleton Continuum Are Associated With the Maturation-Related Adventitious Rooting Competence of Pine Stem Cuttings - Pizarro, Alberto; Díaz-Sala, Carmen (Frontiers in Plant Science, 2022)
Stem cutting recalcitrance to adventitious root formation is a major limitation for the clonal propagation or micropropagation of elite genotypes of many forest tree species, especially at the adult stage of development. The interaction between the cell wall–plasma membrane and cytoskeleton may be involved in the maturation-related decline of adventitious root formation. Here, pine homologs of several genes encoding proteins involved in the cell wall–plasma membrane–cytoskeleton continuum were identified, and the expression levels of 70 selected genes belonging to the aforementioned group and 4 genes encoding auxin carrier proteins were analyzed during adventitious root formation in rooting-competent and non-competent cuttings of Pinus radiata. Variations in the expression levels of specific genes encoding cell wall components and cytoskeleton-related proteins were detected in rooting-competent and non-competent cuttings in response to wounding and auxin treatments. However, the major correlation of gene expression with competence for adventitious root formation was detected in a family of genes encoding proteins involved in sensing the cell wall and membrane disturbances, such as specific receptor-like kinases (RLKs) belonging to the lectin-type RLKs, wall-associated kinases, Catharantus roseus RLK1-like kinases and leucine-rich repeat RLKs, as well as downstream regulators of the small GTP-binding protein family. The expression of these genes was more affected by organ and age than by auxin and time of induction.